Endangered Resources: The Role of Organizational Justice and Interpersonal Trust as Signals for Workplace Corruption - Neveu, Jean-Pierre; Kakavand, Benjamin (Relations industrielles / Industrial Relations, 2019)
This study examines workplace corruption from the perspective of individual psychological processes. Existing literature has shown how corrupt behaviours can emerge from various kinds of motivations, including manipulation, retaliation, and conformity. This research suggests yet another path, where corruption stems from a motivation to preserve resources that individuals perceive to be threatened by their professional environment. As such, the study is grounded in conservation of resources (COR) theory (Hobfoll, 1989, 2001).We put forward an original model that introduces the notion of resource signals. An enrichment of original COR theory, resource signals correspond to individuals’ perceptions that the work environment is supportive, or, otherwise, of their need for resource development and preservation. Specifically, the study tests a moderated mediation model where a sense of mastery, a personal resource, moderates the impact of resource signals, including distributive justice, procedural justice, and interpersonal trust, on occupational corruption.Results are drawn from a sample of French public sector employees (n = 575). They validate the hypothesized mediating role of trust between both facets of organizational justice and measures of corruption, including bribery and property deviance. An indirect negative effect, however, is strongest between procedural justice and workplace corruption. As hypothesized, a sense of mastery significantly moderates the link between trust and both corruption types.This research contributes to both theory and practice. By integrating resource signals within a COR framework, it shows that corrupt behaviours are to be gauged against interacting motivations for preserving psychological resources. Consequently, this study also suggests that organizations should go beyond ethics and procedures, and to consider workplace corruption as a potential symptom of organizational signals perceived as threats to individuals’ valued resources.